Teasing and weight-control behaviors in adolescent girls - Leme,Ana Carolina B. (2013)
OBJECTIVE: To analyze the association between weight teasing, body satisfaction and weight control behaviors. METHODS: Cross-sectional study based on adaptation and validity research of a North American questionnaire for adolescent girls about physical activity, nutrition, body image, perceptions, and behaviors. The variables used to conduct the study were weight control behaviors, body satisfaction and presence of teasing by family members. Descriptive analyses were carried out by chi-square test, being significant p<0.05. RESULTS: A total of 159 adolescent girls, with 16.2±1.3 years old were enrolled in this study. Of the total, 60.1% reported that family members did not tease them. The teasing was associated with weight dissatisfaction (p<0.001), body shape (p=0.006), belly (p=0.001), waist (p=0.001), face (p=0.009), arms (p=0.014) and shoulders (p=0.001). As a consequence, there was association with unhealthy weight control behaviors (p<0.001), vomiting (p=0,011), diet (p=0.002) and use of laxatives (p=0.035). CONCLUSIONS: The teasing about body image by family members was associated with risk for unhealthy weight control behaviors in female adolescents.